2017
DOI: 10.3748/wjg.v23.i21.3825
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-releasing factor stimulates colonic motilityviamuscarinic receptors in the rat

Abstract: AIMTo measure exogenous corticotropin-releasing factor (CRF)-induced motility of the isolated rat colon and to demonstrate the effect of pharmacologic inhibition on CRF-induced motility.METHODSThe isolated vascularly-perfused rat colon was used. Luminal pressure was monitored via microtip catheter pressure transducers in the proximal and distal colon. At first, exogenous CRF was administered in a stepwise manner and the concentration of CRF yielding maximal colonic motility was selected. After recording basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The hypothalamic corticotrophin-releasing hormone (CRF) is considered the main mediator of the psychosocial stress in mammals [ 33 , 34 , 35 , 36 ]. Centrally or peripherally injected, CRF causes adverse intestinal responses that mimic those produced by stress [ 33 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The hypothalamic corticotrophin-releasing hormone (CRF) is considered the main mediator of the psychosocial stress in mammals [ 33 , 34 , 35 , 36 ]. Centrally or peripherally injected, CRF causes adverse intestinal responses that mimic those produced by stress [ 33 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It had been reported that stress increased ACh-induced colon contraction compared to controls [ 8 ]. Also, corticotropin-releasing factor (the main activator of the hypothalamic-pituitary-adrenal axis under stress) increased colonic motility and this effect could be inhibited by atropine pre-treatment, suggesting that cholinergic signaling is involved through muscarinic receptors [ 25 ]. Corticotropin-releasing factor also stimulated propulsive colonic motor function and diarrhea in rats [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a key regulatory factor in the stress reaction, CRF can produce a series of biological effects, such as removing the system to consent stress excitation, accommodating endocrine, autonomic nerve, immunifaction, and regulating behavioral response [ 25 ]. Combining with its receptor, CRF could keep gastrointestinal motility in a stringent state, which accelerates colonic transmission and causes watery diarrhea [ 26 , 27 ]. During colonic dynamo-actuation, the nucleus of the hypothalamus and locus caeruleus were major locus to stimulate colonic movement.…”
Section: Discussionmentioning
confidence: 99%